The Effect of Benson's Relaxation on Pain in Patients Post Open Reduction Internal Fixation Extremity Fractures - Fatikha, Dina; Nurmawati, Thatit (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2023)
The most common complaint felt by patients due to fractures and the main complaint of patients after surgery is pain. Pain that is felt continuously can result in clinical and psychological changes. Benson's relaxation can be an alternative intervention in patients with Post Open Reduction Internal Fixation (ORIF) limb fractures to reduce pain by stimulating the pituitary gland to release endorphins and inhibit pain impulses from the cerebral cortex and thalamus. Benson Relaxation is safe and easy to do, has no risk of injury/side effects. The purpose of this study was to determine the effect of Benson relaxation on pain in patients with Post Open Reduction Internal Fixation (ORIF) limb fractures in the Dahlia Room at Mardi Waluyo General Hospital, Blitar. The research design uses a quasi-experimental pre-post test design. The population was all post ORIF patients with extremity fractures in the Dahlia (surgical) room at Mardi Waluyo Blitar Hospital with a total of 35 patients. The sample was post ORIF extremity fracture patients in the Dahlia Room of Mardi Waluyo General Hospital Blitar with a total sample of 13 respondents in each group using the Consecutive Sampling technique. Pain measurement data uses a Numerical Rating Scale. Statistical test using independent t-test. The results showed that the mean decrease in pain score in the Benson relaxation intervention group was 1.10, while the mean decrease in pain score in the control group was 0.44 with a pvalue of 0.00 < 0.05. It was concluded that there was an effect of Benson relaxation on pain in patients with Post Open Reduction Internal Fixation (ORIF) limb fractures. Benson relaxation is effective in reducing pain in patients with post open reduction internal fixation (ORIF) limb fractures. There needs to be a standard operating procedure regarding Benson's relaxation, so that later it can be implemented by all nurses.Keywords: Benson Relaxation, Pain, Fracture, Post ORIF